416. BIOMARKER IDENTIFICATION FOR CHEMOTHERAPY RESPONSE PREDICTION IN BARRETT'S CARCINOMA PATIENTS BY AN INFLAMMATORY-RELATED PLASMA PROTEIN PROFILING. (24th September 2022) - Thieme, René; Mehdorn, Matthias; Netto, Jeffrey; Schierle, Katrin; Lordick, Florian; Thiery, Joachim; Gockel, Ines
Abstract: The prognosis of patients with advanced esophageal adenocarcinoma (EAC) is still poor, which is partly due to a limited chemotherapy response. About 50% of these patients, treated with neoadjuvant chemotherapy, are non-responder, which might by influenced by inflammation and immunological conditions. EAC patients (n = 24) were characterized prospectively in a single center study for gender (female n = 4; male n = 20), age (median 64; range 43-77 years), TNM-classification, and pathological response rate (PRR) to neoadjuvant chemotherapy. PRR was assessed according to the Schneider classification (Grade 3 + 4 total + subtotal remissions were defined as good responders). A comprehensive high performance inflammation biomarker panel, including 92 inflammatory-related proteins, was conducted in plasma (OLINK, Uppsala, Sweden). Blood was taken before neoadjuvant chemotherapy induction (baseline) and after chemotherapy completion. EAC cell lines (OE33, OE19, SK-GT-4, FLO-1) were treated with the chemokine (C-X3-C motif) ligand 1 (CX3CL1) for 48 h. Nineteen inflammatory-related proteins were altered significantly after neoadjuvant chemotherapy completion. The five most affected proteins were TNF, IFNγ, CX3CL1, FLT3L, and PD-L1. Pathway analyses revealed an activated IL10- and IL18-signalling pathway, after neoadjuvant chemotherapy. A PRR of 3 and 4 correlated significantly with higher baseline CX3CL1 values. CX3CL1 treatment led to decreased proliferation rates in two (OE19 and SK-GT-4) of the four investigated EAC cell lines by 25-50%. Values for GDNF were higher, while values for TRAIL and TNFRSR9 were lower in patients' plasma with a good PRR after chemotherapy completion as compared to patients with a poor PRR. Multiplex profiling of inflammatory-related biomarkers revealed an activated interleukin signaling, (IL10- and IL18 pathway) after neoadjuvant chemotherapy. Inflammatory plasma proteins as CX3CL1 could be an interesting candidate to predict PRR and to identify patients, who will benefit from neoadjuvant chemotherapy. However further prospective studies are needed to validate our first observations.